Asian Fusion - Mingkwan, Chat; Nang Chan Yeema (Boston, Massachusetts USA Book of Publcation Company, 2010)
In Asian Fusion, Chat Mingkwan faithful vegetable translations of signature dishes from all corners of the Asian continent. Readers will get information on how to use and where to find herbs and spices unique to this area and will enjoy Chat's practical approach to creating authentic Asian flavors in Western Kitchens.
Keywords: Adult Nonfiction